Fabrication of 'finger-geometry' silicon solar cells by electrochemical anodisation - Martins, G; Thompson, A; Goller, B; Kovalev, D; Murphy, J (2013)
Cells made from crystalline silicon dominate the market for photovoltaics, but improvements in cost-effectiveness are still necessary for uptake to increase. In this paper, we investigate the fabrication of a cell structure which has the potential to be compatible with cheap low-purity silicon substrates. In our cell design the charge-collecting p-n junction protrudes into the substrate like fingers, thus significantly reducing the required carrier diffusion length compared to a front planar junction cell. The macroporous structure is created by electrochemical anodisation of an n-type silicon substrate in an HF and H2O2 (aqueous) electrolyte. The pores are loaded with a boron-containing glass which is then annealed to diffuse the dopant into the silicon substrate forming a volume junction. The anodisation conditions have been optimised using intentionally contaminated single-crystal silicon as a model system. We characterise the junction formed by electron beam induced current and current-voltage measurements. The anodisation study is extended to n-type multicrystalline silicon and it is found that the orientation of the grains strongly influences the geometry of the pores formed. The potential for using this cell structure for low-cost photovoltaics is discussed and potential problems are highlighted. © 2012 Springer Science+Business Media.